Patterns of Social Interaction of Papuan Students (Case Study at Public Vocational High School 2 Purwodadi, Grobogan Regency) - Yulistyawan, Nanang Eko; Raharjo, Tri Joko; Alimi, Moh Yasir (JESS (Journal of Educational Social Studies), 2019)
Based on preliminary observations at Public Vocational High School 2 Purwodadi, Grobogan Regency related to the interaction of Papuan students is not in line with what was expected, where the process of social interaction is not running through contact and communication. The purpose of this study are to identify patterns of social interaction of Papuan students, identify the constraints of social interaction of Papuan students and analyze school strategies in encouraging the process of social interaction of Papuan students at Public Vocational High School 2 Purwodadi. Research methods using qualitative approach. The determination of informants is chosen according to the focus that will be discussed in this study. Criteria for determining informants are informants who understand and are related to existing research problems. The instrument used in this study was a list of questions, or what is called an interview instrument. Data collection techniques used were observation, interviews, and documentation. The data validity technique uses triangulation techniques. Based on the results of the study, it was found that the pattern of social interaction of Papuan students at Public Vocational High School 2 Purwodadi, in general, has been going well even though some obstacles must be immediately sought a solution. The hope to be achieved is the occurrence of harmonious and synergistic relationships in the process of social interaction so that it supports the education program launched by the government.